A Conjugated Covalent Template Strategy for All‐Benzene Catenane Synthesis. Issue 39 (19th August 2022) - Bu, An; Zhao, Yongye; Xiao, Hongyan; Tung, Chen‐Ho; Wu, Li‐Zhu; Cong, Huan
Abstract: Mechanically interlocked molecules based on oligoparaphenylene‐derived nanohoops, particularly those without heteroatoms, are synthetically challenging and topologically intriguing targets. Herein, a π‐conjugated covalent template strategy based on azo group has been developed, which features dual intramolecular macrocyclizations directed by a tetra‐substituted azobenzene core, followed by traceless removal of the azo linker. Employing this strategy, the efficient synthesis of a novel all‐benzene [2]catenane consisting of meta ‐cycloparaphenylenes has been accomplished. Abstract : Heteroatom‐free catenanes are synthetically non‐trivial targets, and especially those composed of highly strained oligoparaphenylene‐derived nanohoops. Herein, a novel conjugated covalent template strategy employing an azo group is established for an efficient synthesis of an all‐benzene catenane. It features azobenzene‐directed dual intramolecular macrocyclizations and traceless removal of the azo template.